Nursing students' experiences of clinical assessment at a university in South Africa - Gabieba Donough (AOSIS, 2023)
Background: Nursing education includes both classroom and clinical teaching. The clinical teaching was explored through this research. The successful training of the undergraduate nursing students can be attributed to effective clinical teaching and supervision and is determined by both training requirements and services provided. Although there have been several researches on clinical supervision, there is still a dearth of information of the realities of supervision regarding assessment of undergraduate nursing students. The authors' original thesis formed the foundation of this manuscript. Aim: This study aimed to explore and describe nursing students at the undergraduate level experiences regarding clinical supervision. Setting: The research was conducted at a nursing school at a South African university. Method: After ethical clearance, focus group interviews were conducted to explore undergraduate nursing students' experiences of clinical supervision using a descriptive design and qualitative approach. Two qualified practitioners in the field collected the data. A purposive method was utilised to select nine participants from each year's level of education. Enrolled undergraduate nursing students at the institution under study formed the inclusion criteria. Utilising content analysis, the interviews were analysed. Results: The findings confirmed the students' experiences of clinical supervision and voicing their concerns regarding clinical assessment versus a developmental training; clinical teaching, learning and assessment and formative assessment procedures. Conclusion: A responsive clinical supervision system to strategically respond to the needs of undergraduate nursing students will aid in developmental training and assessment. Contribution: Understanding of the realities of clinical teaching and supervision regarding clinical assessment and development of undergraduate nursing students.